COSTS AND BENEFITS OF SMOKING RESTRICTIONS IN THE WORKPLACE (Tufts Archival Research Center, 2007)
Missing Page(s); Interview with William Weis of Seattle University regarding the costs and benefits of smoking restrictions in the workplace. Remarks that it is possible to save money by restricting smoking but that this is not the main reason employers implement no smoking policies. Addresses costs to the employer.